The financialization of Danish cooperatives and the debasement of a collective housing good. (June 2018) - Bruun, Maja Hojer
The article tells the story of Danish cooperative housing's radical transformation from a collective housing good and commons to a financialized asset during the 2000s when neoliberal housing reforms were introduced and the mortgage finance market was deregulated. Processes of financialization of collectively owned housing have to be understood not only in relation to the dynamics of the surrounding housing market and political-economic changes but also to the communities and social relations that they presuppose and feed off, often in contradictory ways, as people are motivated by both solidarity and private interests. Housing cooperatives have existed as a form of collective housing throughout the 20th century, balanced, on the one hand, between the reproduction of kin, family and local communities and the common good and, on the other, between the market and the reproduction of the base for both families, local communities and the larger public sharing the housing commons. During the 2000s, processes of financialization brought the market and the cooperatives' base so close together, primarily through new mortgaging opportunities, that families and communities have lost their savings and the base has been undermined, both in a material and an immaterial sense.